Analysis of Factors Affecting Students' Intention in Using Learning Management System Applications in the Senior High School Environment - Bororing, Agri Adriel (Universitas Syiah Kuala, 2025)
In today's digital era, mobile applications play a crucial role in supporting students' academic activities. Many high schools have introduced their own Learning Management System (LMS) applications to enhance accessibility to academic resources. However, the adoption of these applications remains limited. This study seeks to examine the factors influencing students' intention to use LMS applications by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The examined variables include Effort Expectancy, Performance Expectancy, Social Influence, Satisfaction, and Trust. The findings indicate that Social Influence, Satisfaction, and Trust significantly impact students' intention to use LMS applications, whereas Effort Expectancy and Performance Expectancy do not show a notable effect to student intention to use LMS.